The Influence of Empowering Leadership Towards Employee Ambidexterity : Study Literature Review - Fortunisa, Ananda; Putri, Dianingtyas M.; Elsyah, Riska Dwinda (Journal of The Community Development in Asia, 2023)
Employee ambidexterity has been viewed as the crucial variable in measuring the employee's innovation and creativity. Therefore, the discussion of employee ambidexterity is essential in supporting the literature about employee creativity and innovation. However, the discussion about the factors affect employee ambidexterity in the literature study is still limited.  Based on the existing studies, one of the critical factors that influence the creativity and innovation of employees at work is the leadership factor. This study will specifically analyze the effect of empowering leadership on employee ambidexterity based on a literature review that has never been discussed before. This research method uses a literature review by comprehensively comparing and reviewing on these two variables from 28 scopus journals. The results of this study found four dimensions of empowering leadership: the meaning of work, encouragement of employee participation, expression of beliefs, and work autonomy. In addition, this study also found two dimensions of employee ambidexterity: exploration and exploitation. In addition, these findings explain the characteristics, influences, and factors between the two variables and how empowering leadership can increase employee ambidexterity. This study suggests the company develop empowering leadership as the leadership style to improve employee ambidexterity.